High-performance modified zinc-aluminum anticorrosive coating and preparation method thereof
Through wet ball milling treatment and composite nanomaterial coating technology, zinc-aluminum powder is modified, which solves the problem that existing zinc-aluminum coating liquid requires high-temperature curing, achieves low-temperature curing, reduces production energy consumption and costs, and increases the Economic benefits and environmental protection.
Patent Information
- Application Number
- CN202411652056.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-based environmentally friendly zinc-aluminum coating liquid needs to be cured at high temperature in production and application, resulting in high energy consumption, low efficiency, high cost, poor economic benefits and environmental protection.
The zinc powder and aluminum powder were treated by wet ball milling, and the sheet-shaped zinc-aluminum alloy was coated and passivated with composite nanomaterials to make modified zinc-aluminum powder and cured under normal temperature conditions.
The low-temperature curing and room-temperature curing of the coating is achieved, which reduces production energy consumption, improves production efficiency, saves costs, and significantly improves the economic benefits and environmental protection of the coating.
Abstract
Description
Technical Field
[0001] The invention relates to the field of anti-corrosion coatings, in particular to a high-performance modified zinc-aluminum anti-corrosion coating, and also to a preparation method of the anti-corrosion coating. Background Art
[0002] Water-based environmentally friendly zinc-aluminum coatings have been widely used in fasteners, automobiles, wind power, photovoltaics, rail transit and other fields due to their thin coating, salt spray resistance, and high temperature resistance. They play an irreplaceable protective role. Zinc-aluminum coatings protect the substrate due to their unique properties. However, the metallic activity of zinc and aluminum determines that zinc and aluminum powders cannot be dispersed stably in the aqueous system for a long time. Therefore, a large amount of surfactants must be used to emulsify and coat them. In the existing water-based environmentally friendly zinc-aluminum coating system, the surfactant must be sintered at a temperature of 300 to 350°C, so that flaky zinc powder and flaky aluminum powder can play a protective role in the entire system as a physical barrier, anode sacrifice, substrate passivation and self-repairing functions. As a result, the coating cannot be cured at low temperature during production and application, and needs to be assisted by high temperature, resulting in high production energy consumption, low efficiency, high cost, and poor economic benefits and environmental protection. Summary of the invention
[0003] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a high-performance modified zinc-aluminum anti-corrosion coating and a preparation method thereof to prepare a coating that can be cured at low temperature and room temperature, so that the coating liquid can be developed in the field of industrial corrosion protection in the long term.
[0004] A high-performance modified zinc-aluminum anti-corrosion coating, the anti-corrosion coating comprises the following components: modified zinc-aluminum powder, graphene oxide, nano-silicon dioxide, polyamide wax, an organosilicon wetting agent and an organic solvent are mixed in proportion to obtain the anti-corrosion coating; wherein the modified zinc-aluminum powder is obtained by wet ball milling zinc powder and aluminum powder in a ratio of 2:1.
[0005] As a further improvement of the above scheme, the anti-corrosion coating is composed of the following by weight: 15% to 45% modified zinc-aluminum powder, 0.5% to 3% graphene oxide, 2% to 7% nano-silicon dioxide, 1% to 3% polyamide wax, 0.2% to 1% silicone wetting agent, and 40% to 82% organic solvent.
[0006] As a further improvement of the above scheme, the anti-corrosion coating is composed of the following by weight: 35% modified zinc-aluminum powder, 2% graphene oxide, 5% nano-silicon dioxide, 2% polyamide wax, 0.5% organosilicon wetting agent, and 55.5% organic solvent.
[0007] As a further improvement of the above scheme, the organic solvent is any one of isopropanol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol dimethyl ether, m-phenylenediamine, p-propylene glycol methyl ether and ethylene glycol butyl ether.
[0008] A coating preparation method, which is used to prepare the anti-corrosion coating, comprises the following steps:
[0009] S1 wet-ball-mills the zinc powder and the aluminum powder to obtain a slurry;
[0010] S2 performs filter pressing on the slurry and retains the filter cake;
[0011] S3: using graphene oxide, nano-silicon dioxide and polyamide wax to coat the aluminum and zinc in the filter cake to obtain a composite coated zinc-aluminum alloy slurry;
[0012] S4 performs filter pressing on the composite coated zinc-aluminum alloy slurry to retain the filter cake;
[0013] S5: putting the filter cake into a kneader, adding an organosilicon wetting agent and an organic solvent in sequence, and mixing to obtain a coating.
[0014] As a further improvement of the above scheme, the wet ball milling method is specifically operated as follows:
[0015] S11: aluminum powder, zinc powder, stearic acid, coupling agent, No. 200 solvent oil and surface modifier are prepared to prepare a mixed solution;
[0016] S12: Take a carbide grinding ball and add it to the mixed solution, and ball mill it for 10 to 16 hours.
[0017] As a further improvement of the above scheme, the mass composition of the mixed solution is as follows: 20% aluminum powder, 10% zinc powder, 2% stearic acid, 0.5% coupling agent, 65% No. 200 solvent oil, and 2.5% surface modifier. The aluminum powder and zinc powder are both spherical particles, and the particle size of the aluminum powder is 2 to 20 μm, and the particle size of the zinc powder is 20 to 30 μm. The coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent, and a borate coupling agent.
[0018] As a further improvement of the above scheme, the surface modifier uses polyvinyl alcohol, polypropylene alcohol or polybutene alcohol. The present invention refines the metal powder based on ball milling, adds No. 200 oil solvent to form a slurry system, and realizes wet grinding. During ball milling, stearic acid, a solid surfactant, is added to prevent the oxidation of the powder. Stearic acid is adsorbed on the surface of the powder during ball milling to form a film, which hinders the diffusion between atoms and reduces the degree of mechanical alloying of the metal powder during ball milling, thereby obtaining a nano-scale material with good performance. A coupling agent is added to improve the compatibility between metal particles and solvent oil, thereby enhancing the mechanical properties and durability of the composite material. The addition of a surface modifier forms a strong bond with the surface of the aluminum powder, which promotes the dispersion of the aluminum powder in the slurry.
[0019] As a further improvement of the above scheme, grinding balls with diameters of 8 mm, 6 mm, 2 mm and 1 mm are mixed in a ratio of 3:3:2:2 to obtain the cemented carbide grinding balls. The weight ratio of the cemented carbide grinding balls to the mixed solution is 30:1, the temperature of the ball milling treatment is lower than 45°C, and nitrogen is introduced during the ball milling process for protection.
[0020] As a further improvement of the above scheme, the method for obtaining a composite coated zinc-aluminum alloy slurry by coating treatment is specifically performed as follows:
[0021] S31 filter cake is added to the reaction kettle, followed by dipropylene glycol butyl ether and propylene glycol, and mixed by stirring at a low speed to obtain a mixed solution A;
[0022] S32 adding the graphene oxide solution while stirring to obtain a mixed solution B;
[0023] S33 adds the nano-silicon dioxide solution while stirring, and stirs at a medium speed to obtain a mixed solution C;
[0024] S34 adds polyamide wax while stirring, and stirs at high speed to obtain a composite coated zinc-aluminum alloy slurry.
[0025] As a further improvement of the above scheme, the ratio of the filter cake, dipropylene glycol butyl ether and propylene glycol is 8:1:9. In the present invention, dipropylene glycol butyl ether is added as a film-forming aid, so that the subsequently added graphene oxide, nano silicon dioxide and polyamide wax are well combined with aluminum zinc.
[0026] As a further improvement of the above scheme, in S31-S32, the stirring speed is 80-100 r / min, and the stirring time is 30-60 min. Graphene oxide and water are mixed in a ratio of 1:4 to obtain the graphene oxide solution; nano-silicon dioxide and propylene glycol are mixed in a ratio of 1:9 to obtain the nano-silicon dioxide solution. The medium-speed stirring speed is 200-300 r / min, and the high-speed stirring speed is 500-600 r / min; the processing temperature of S31-S34 is 40-60°C.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The coating is a zinc-aluminum pseudo-alloy slurry made by ball-milling the blended spherical zinc powder and spherical aluminum powder, and coating and passivating the flaky zinc-aluminum alloy with composite nanomaterials. The flaky zinc-aluminum powder can be dispersed and stored in an aqueous system stably for a long time, and the coating material does not affect the activity of the zinc-aluminum powder under room temperature curing conditions, so low-temperature and room-temperature curing of the coating can be achieved. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0030] The specific embodiments of the present invention are described in detail below.
[0031] Example 1
[0032] The present embodiment provides a high-performance modified zinc-aluminum anti-corrosion coating, which has the following composition by weight: 15% modified zinc-aluminum powder, 0.5% graphene oxide, 2.5% nano-silicon dioxide, 1% polyamide wax, 0.2% organosilicon wetting agent, and 80.8% isopropyl alcohol.
[0033] The preparation method of the anti-corrosion coating of this embodiment comprises the following steps:
[0034] S1: wet ball milling zinc powder and aluminum powder to obtain slurry.
[0035] The wet ball milling method is specifically performed as follows:
[0036] S11 takes 20% aluminum powder, 10% zinc powder, 2% stearic acid, 0.5% titanate coupling agent 65%, No. 200 solvent oil and 2.5% polyvinyl alcohol to prepare a mixed solution, wherein the aluminum powder and zinc powder are both spherical particles, and the particle size of the aluminum powder is 4 μm, and the particle size of the zinc powder is 30 μm.
[0037] S12 uses grinding balls with diameters of 8 mm, 6 mm, 2 mm and 1 mm, which are mixed in a ratio of 3:3:2:2 to obtain the cemented carbide grinding balls. The cemented carbide grinding balls are added to the mixed solution, the weight ratio of the cemented carbide grinding balls to the mixed solution is 30:1, and the ball milling treatment is performed for 15 hours. The ball milling temperature is lower than 45°C, and nitrogen is introduced for protection during the ball milling process.
[0038] In this embodiment, the metal powder is refined based on ball milling, and a No. 200 oil solvent is added to form a slurry system to achieve wet milling. During ball milling, stearic acid, a solid surfactant, is added to prevent the oxidation of the powder. Stearic acid is adsorbed on the surface of the powder during ball milling to form a film, which hinders the diffusion between atoms and reduces the degree of mechanical alloying of the metal powder during ball milling, thereby obtaining a nano-scale material with good performance. Titanate coupling agent is added to improve the compatibility between metal particles and solvent oil, thereby enhancing the mechanical properties and durability of the composite material. Polyvinyl alcohol is added to form a strong bond with the surface of aluminum powder, which promotes the dispersion of aluminum powder in the slurry.
[0039] S2 filter presses the slurry to separate the solid and liquid, and obtains a filter cake with 75% solid content. The filtrate is recovered for the next ball milling.
[0040] S3 takes 0.5% graphene oxide, 2.5% nano-silicon dioxide and 1% polyamide wax to coat the aluminum and zinc in the filter cake to obtain a composite coated zinc-aluminum alloy slurry. In this embodiment, graphene oxide is used to coat the flaky zinc powder and flaky aluminum powder, nano-silicon dioxide is used to coat the flaky zinc powder and flaky aluminum powder, and polyamide wax is used to surface treat the flaky zinc powder and flaky aluminum powder. The polyamide wax plays a role in rheological thickening and forms a strong network structure in the coating. By utilizing its excellent thixotropic properties, the coating has excellent anti-sagging and anti-settling capabilities.
[0041] The method for obtaining the composite coated zinc-aluminum alloy slurry by coating treatment is specifically performed as follows:
[0042] S31 filter cake is added to the reactor, and then dipropylene glycol butyl ether and propylene glycol are added, the ratio of the filter cake, dipropylene glycol butyl ether and propylene glycol is 8:1:9, the modified zinc aluminum powder accounts for 15% of the filter cake, and the mixture is stirred at a low speed to obtain a mixed solution A. In this embodiment, dipropylene glycol butyl ether is used as a film-forming aid, so that the graphene oxide, nano silicon dioxide and polyamide wax added subsequently are well combined with aluminum and zinc.
[0043] S32 Graphene oxide and water are mixed in a ratio of 1:4 to obtain a graphene oxide solution, and the graphene oxide solution is added while stirring to obtain a mixed solution B.
[0044] S33 nano-silica and propylene glycol were mixed in a ratio of 1:9 to obtain a nano-silica solution, and the nano-silica solution was added while stirring, and mixed solution C was obtained by stirring at a medium speed.
[0045] S34 adds polyamide wax while stirring, and stirs at high speed to obtain a composite coated zinc-aluminum alloy slurry.
[0046] In S31-S32, the stirring speed is 80 r / min, the stirring time is 50 min, the medium-speed stirring speed is 250 r / min, the high-speed stirring speed is 500 r / min, and the processing temperature of S31-S34 is 50°C.
[0047] S4 filter press composite coated zinc-aluminum alloy slurry for solid-liquid separation, filter press to obtain 85% solid content of the filter cake, the filtrate is recovered for the next coating use.
[0048] S5: Put the filter cake into a kneader, add 0.2% of silicone wetting agent and 80.8% of isopropyl alcohol in sequence, and mix to obtain a coating. In this embodiment, the filter cake, silicone wetting agent and isopropyl alcohol are evenly mixed based on the kneading process to form a coating with a certain viscosity, and the silicone wetting agent is used to pre-treat the surface of the flaky zinc powder and the flaky aluminum powder. This embodiment is explained by taking the addition of Tego4100 silicone wetting agent as an example. The silicone wetting agent plays a role in wetting the substrate when the coating is applied.
[0049] Example 2
[0050] The present embodiment provides a high-performance modified zinc-aluminum anti-corrosion coating, which has the following composition by weight: 35% modified zinc-aluminum powder, 2% graphene oxide, 5% nano-silicon dioxide, 2% polyamide wax, 0.5% silicone wetting agent, and 55.5% isopropyl alcohol.
[0051] The preparation method of the anti-corrosion coating of this embodiment comprises the following steps:
[0052] S1: wet ball milling zinc powder and aluminum powder to obtain slurry.
[0053] The wet ball milling method is specifically performed as follows:
[0054] S11 takes 20% aluminum powder, 10% zinc powder, 2% stearic acid, 0.5% titanate coupling agent 65%, No. 200 solvent oil and 2.5% polyvinyl alcohol to prepare a mixed solution, wherein the aluminum powder and zinc powder are both spherical particles, and the particle size of the aluminum powder is 4 μm, and the particle size of the zinc powder is 30 μm.
[0055] S12 uses grinding balls with diameters of 8 mm, 6 mm, 2 mm and 1 mm, which are mixed in a ratio of 3:3:2:2 to obtain the cemented carbide grinding balls. The cemented carbide grinding balls are added to the mixed solution, the weight ratio of the cemented carbide grinding balls to the mixed solution is 30:1, and the ball milling treatment is performed for 15 hours. The ball milling temperature is lower than 45°C, and nitrogen is introduced for protection during the ball milling process.
[0056] S2 filter presses the slurry to separate the solid and liquid, and obtains a filter cake with 75% solid content. The filtrate is recovered for the next ball milling.
[0057] S3 takes 2% graphene oxide, 5% nano-silicon dioxide and 2% polyamide wax to coat the aluminum and zinc in the filter cake to obtain a composite coated zinc-aluminum alloy slurry.
[0058] The method for obtaining the composite coated zinc-aluminum alloy slurry by coating treatment is specifically performed as follows:
[0059] S31 filter cake is added to the reactor, and then dipropylene glycol butyl ether and propylene glycol are added. The ratio of the filter cake, dipropylene glycol butyl ether and propylene glycol is 8:1:9, and the modified zinc-aluminum powder accounts for 35% of the filter cake. The mixture is stirred at a low speed to obtain a mixed solution A.
[0060] S32 Graphene oxide and water are mixed in a ratio of 1:4 to obtain a graphene oxide solution, and the graphene oxide solution is added while stirring to obtain a mixed solution B.
[0061] S33 nano-silica and propylene glycol were mixed in a ratio of 1:9 to obtain a nano-silica solution, and the nano-silica solution was added while stirring, and mixed solution C was obtained by stirring at a medium speed.
[0062] S34 adds polyamide wax while stirring, and stirs at high speed to obtain a composite coated zinc-aluminum alloy slurry.
[0063] In S31-S32, the stirring speed is 80 r / min, the stirring time is 50 min, the medium-speed stirring speed is 250 r / min, the high-speed stirring speed is 500 r / min, and the processing temperature of S31-S34 is 50°C.
[0064] S4 filter press composite coated zinc-aluminum alloy slurry for solid-liquid separation, filter press to obtain 85% solid content of the filter cake, the filtrate is recovered for the next coating use.
[0065] S5: putting the filter cake into a kneader, adding 0.5% of an organosilicon wetting agent and 55.5% of isopropyl alcohol in sequence, and mixing to obtain a coating.
[0066] Example 3
[0067] The present embodiment provides a high-performance modified zinc-aluminum anti-corrosion coating, which has the following composition by weight: 45% modified zinc-aluminum powder, 3% graphene oxide, 7% nano-silicon dioxide, 3% polyamide wax, 1% silicone wetting agent, and 41% isopropyl alcohol.
[0068] The preparation method of the anti-corrosion coating of this embodiment comprises the following steps:
[0069] S1: wet ball milling zinc powder and aluminum powder to obtain slurry.
[0070] The wet ball milling method is specifically performed as follows:
[0071] S11 takes 20% aluminum powder, 10% zinc powder, 2% stearic acid, 0.5% titanate coupling agent 65%, No. 200 solvent oil and 2.5% polyvinyl alcohol to prepare a mixed solution, wherein the aluminum powder and zinc powder are both spherical particles, and the particle size of the aluminum powder is 4 μm, and the particle size of the zinc powder is 30 μm.
[0072] S12 uses grinding balls with diameters of 8 mm, 6 mm, 2 mm and 1 mm, which are mixed in a ratio of 3:3:2:2 to obtain the cemented carbide grinding balls. The cemented carbide grinding balls are added to the mixed solution, the weight ratio of the cemented carbide grinding balls to the mixed solution is 30:1, and the ball milling treatment is performed for 15 hours. The ball milling temperature is lower than 45°C, and nitrogen is introduced for protection during the ball milling process.
[0073] S2 filter presses the slurry to separate the solid and liquid, and obtains a filter cake with 75% solid content. The filtrate is recovered for the next ball milling.
[0074] S3 takes 3% graphene oxide, 7% nano-silicon dioxide and 3% polyamide wax to coat the aluminum and zinc in the filter cake to obtain a composite coated zinc-aluminum alloy slurry.
[0075] The method for obtaining the composite coated zinc-aluminum alloy slurry by coating treatment is specifically performed as follows:
[0076] S31 filter cake is added to the reactor, and then dipropylene glycol butyl ether and propylene glycol are added. The ratio of the filter cake, dipropylene glycol butyl ether and propylene glycol is 8:1:9, and the modified zinc-aluminum powder accounts for 45% of the filter cake. The mixture is stirred at a low speed to obtain a mixed solution A.
[0077] S32 Graphene oxide and water are mixed in a ratio of 1:4 to obtain a graphene oxide solution, and the graphene oxide solution is added while stirring to obtain a mixed solution B.
[0078] S33 nano-silica and propylene glycol were mixed in a ratio of 1:9 to obtain a nano-silica solution, and the nano-silica solution was added while stirring, and mixed solution C was obtained by stirring at a medium speed.
[0079] S34 adds polyamide wax while stirring, and stirs at high speed to obtain a composite coated zinc-aluminum alloy slurry.
[0080] In S31-S32, the stirring speed is 80 r / min, the stirring time is 50 min, the medium-speed stirring speed is 250 r / min, the high-speed stirring speed is 500 r / min, and the processing temperature of S31-S34 is 50°C.
[0081] S4 filter press composite coated zinc-aluminum alloy slurry for solid-liquid separation, filter press to obtain 85% solid content of the filter cake, the filtrate is recovered for the next coating use.
[0082] S5: Put the filter cake into a kneader, add 1% of an organosilicon wetting agent and 41% of isopropyl alcohol in sequence, and mix to obtain a coating.
[0083] The anti-corrosion coating of Example 2 is the optimal component. Different from Example 2, the anti-corrosion coating of Example 1 has the lowest zinc and aluminum content, while the anti-corrosion coating of Example 3 has the highest zinc and aluminum content.
[0084] Take a certain automobile brake disc manufacturer in Shandong as an example. During production, after the workpiece is sprayed with the anti-corrosion coating of Example 2, it is baked at 120°C for 30 minutes and forced to cool for 15 minutes before being packaged offline. Without the anti-corrosion coating of the present invention, the workpiece needs to be baked at 350°C for 40 minutes after being sprayed with the coating, and then forced to cool for 30 minutes. At the same time, a neutral salt spray test is conducted with a workpiece made of other anti-corrosion coatings as a control group and a workpiece made of the anti-corrosion coating of Example 2. In a specific test box, salt water is sprayed through a spray device to allow the salt spray to settle on the test piece to be tested. After a certain period of time, its surface corrosion state is observed. The specific test process is not described in detail here. The test result is that the neutral salt spray time of the product has been increased from the original 96h to more than 240h.
[0085] The above comparison proves that when the anti-corrosion coating of the present invention is used in the coating protection of workpieces, the comprehensive energy consumption of production is reduced by more than 50%, carbon emissions are reduced by more than 50%, production efficiency is increased by more than 30%, costs are saved by more than 30%, the economic and social benefits are significant, and the prospects for promotion and application are excellent.
[0086] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A high performance modified zinc-aluminum anti-corrosion coating, characterized in that: The anti-corrosion coating comprises the following components: modified zinc aluminum powder, graphene oxide, nano silicon dioxide, polyamide wax, organosilicon wetting agent and organic solvent are mixed in proportion to obtain the anti-corrosion coating; The modified zinc-aluminum powder is obtained by wet ball milling zinc powder and aluminum powder in a ratio of 2:
1.
2. The high performance modified zinc-aluminum anti-corrosion coating according to claim 1, characterized in that: The anti-corrosion coating is composed of the following by weight: 15% to 45% of modified zinc-aluminum powder, 0.5% to 3% of graphene oxide, 2% to 7% of nano silicon dioxide, 1% to 3% of polyamide wax, 0.2% to 1% of organic silicon wetting agent, and 40% to 82% of organic solvent.
3. The high performance modified zinc-aluminum anti-corrosion coating according to claim 2, characterized in that: The anti-corrosion coating is composed of the following by weight: 35% of modified zinc-aluminum powder, 2% of graphene oxide, 5% of nano silicon dioxide, 2% of polyamide wax, 0.5% of organic silicon wetting agent and 55.5% of organic solvent.
4. The high performance modified zinc-aluminum anti-corrosion coating according to claim 3, characterized in that: The organic solvent is any one of isopropanol, ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol dimethyl ether, m-phenylenediamine, p-propylene glycol methyl ether and ethylene glycol butyl ether.
5. A coating preparation method, which is used to prepare the anti-corrosion coating according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1 wet-milling the zinc powder and the aluminum powder to obtain a slurry; S2 performs filter pressing on the slurry and retains the filter cake; S3: using graphene oxide, nano-silicon dioxide and polyamide wax to coat the aluminum and zinc in the filter cake to obtain a composite coated zinc-aluminum alloy slurry; S4 performs filter pressing on the composite coated zinc-aluminum alloy slurry to retain the filter cake; S5: putting the filter cake into a kneader, adding an organosilicon wetting agent and an organic solvent in sequence, and mixing to obtain a coating.
6. The coating preparation method according to claim 5, characterized in that: The wet ball milling method is specifically performed as follows: S11: aluminum powder, zinc powder, stearic acid, coupling agent, No. 200 solvent oil and surface modifier are prepared to prepare a mixed solution; S12: Take a carbide grinding ball and add it to the mixed solution, and ball mill it for 10 to 16 hours.
7. The coating preparation method according to claim 6, characterized in that: The mixed solution is composed of 20% aluminum powder, 10% zinc powder, 2% stearic acid, 0.5% coupling agent, 65% No. 200 solvent oil, and 2.5% surface modifier by mass; the aluminum powder and zinc powder are both spherical particles, and the particle size of the aluminum powder is 2-20 μm, and the particle size of the zinc powder is 20-30 μm; The coupling agent is any one of a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, a phosphate coupling agent and a borate coupling agent; and the surface modifier is polyvinyl alcohol, polypropylene alcohol or polybutene alcohol.
8. The coating preparation method according to claim 7, characterized in that: Grinding balls with diameters of 8 mm, 6 mm, 2 mm and 1 mm are mixed in a ratio of 3:3:2:2 to obtain the cemented carbide grinding balls; The weight ratio of the cemented carbide grinding balls to the mixed solution is 30:1, the temperature of the ball milling treatment is lower than 45° C., and nitrogen is introduced during the ball milling process for protection.
9. The coating preparation method according to claim 8, characterized in that: The method for obtaining the composite coated zinc-aluminum alloy slurry by coating treatment is specifically performed as follows: S31 filter cake is added to the reaction kettle, followed by dipropylene glycol butyl ether and propylene glycol, and mixed by stirring at a low speed to obtain a mixed solution A; S32 adding the graphene oxide solution while stirring to obtain a mixed solution B; S33 adds the nano-silicon dioxide solution while stirring, and stirs at a medium speed to obtain a mixed solution C; S34 adds polyamide wax while stirring, and stirs at high speed to obtain a composite coated zinc-aluminum alloy slurry.
10. The coating preparation method according to claim 9, characterized in that: The ratio of the filter cake, dipropylene glycol butyl ether and propylene glycol is 8:1:9; in S31-S32, the stirring speed is 80-100 r / min, and the stirring time is 30-60 min; Graphene oxide and water are mixed in a ratio of 1:4 to obtain the graphene oxide solution; nano-silicon dioxide and propylene glycol are mixed in a ratio of 1:9 to obtain the nano-silicon dioxide solution; The medium-speed stirring speed is 200-300 r / min, and the high-speed stirring speed is 500-600 r / min; the processing temperature of S31-S34 is 40-60°C.